Nigerian Undergraduates’ Awareness of Self-Regulation Strategies in ESL Academic Writing - Muhktar, Muhammad; Yau, Mohammed Sani; Garba, Sadia Inuwa; Yakubu , Halima Sadiya (STAIN Majene, 2023)
This research focuses on investigating the awareness and perception of self-regulation strategies in academic writing among undergraduate students. Specifically, it aims to explore the level of undergraduates' awareness in various aspects of self-regulation, such as goal setting, adopting powerful strategies, self-monitoring, restructuring social and physical context, time management, self-evaluation, attributing causation to results, and adapting future methods. The study adopts a cross-sectional survey research design and includes a sample of eighty-seven (87) third-year undergraduates majoring in English in Nigeria. To collect data, a questionnaire was employed as the primary research instrument. The data collected were analyzed using the SPSS software to address the research questions of the study. The findings indicate the respondents’ moderate level of awareness regarding self-regulation strategies in ESL academic writing. This moderate level of awareness cuts across all aspects of self-regulation analyzed in this study. Based on the study's findings, several recommendations are proposed for both practical implementation and future research. These recommendations aim to enhance undergraduates' awareness of self-regulation strategies in ESL academic writing and improve their overall writing skills. Further studies are also suggested to delve deeper into the effectiveness and impact of various self-regulation strategies on undergraduate students' academic writing performance.